FACTORS INFLUENCING NIVEA FACE WASH PURCHASING DECISION IN CIKARANG - Primaraga Sumantri Indra Wicaksana; Surya Bintarti (Jurnal Ekonomi, 2023)
This study intends to find out what factors can influence consumer decisions to buy Nivea face wash soap in Cikarang. Quantitative research is the method used. Nonprobability sampling with accidental sampling methodology is a sampling technique with a sample size of 100 people. The general public in South Cikarang who use Nivea facial cleansing soap are the research samples. SPSS software version 25 was used in this investigation. The analytical approach used includes the normality test, multiple regression, t test, and the coefficient of determination. Based on all of the above tests regarding the effect of brand image on purchasing decisions, the results obtained are sig greater than 0.05, namely 0.157, and the t-count value is 1.426 with t-table less than 1.660, this indicates that this has a negative impact on the brand image but not significant to the purchase decision. Based on all the tests that have been carried out above concerning the effect of product quality on purchasing decisions, it can be seen from the research findings that there is a significant positive effect on product quality and the sig value of 0.001 is less than 0.05 and that the calculated t value is 3.557 with t table 1.660 . Based on all the tests that have been carried out to determine the effect of price on purchasing decisions, it is clear from the findings of this study that there is a positive and significant price effect on the decision. The calculated t value is 5.720 with t table 1.660, and the sig value of 0.000 is less than 0.05.